A Prospective Observational Study of Video Laryngoscopy Use in Difficult Airway Management. (25th March 2020) - Hyman, Jaime B.; Apatov, David; Katz, Daniel; Levine, Adam I.; DeMaria, Samuel
Abstract : Objectives/Hypothesis: Video laryngoscopy has grown tremendously in popularity over the last decade for management of the anticipated difficult airway. The use of video laryngoscopy has not been adequately studied in the head and neck pathology patient population, including those with masses, previous head and neck surgery, or radiation. Study Design: Prospective observational study. Methods: This study included 100 patients with head and neck pathology undergoing awake flexible bronchoscopic intubation for nonemergency surgery requiring general anesthesia. After the performance of awake flexible bronchoscopic intubation and induction of anesthesia, video laryngoscopy was performed with the CMAC D blade and Glidescope AVL. The primary outcome was the modified Cormack‐Lehane view obtained on video laryngoscopy. Results: One hundred patients were enrolled in the study. After exclusions, 92 patients underwent video laryngoscopy with both the CMAC D blade and the Glidescope AVL. Thirty‐seven patients (40.2%) had a Cormack‐Lehane view ≥3 with the CMAC D blade, and 28 patients (30.4%) had a Cormack‐Lehane view ≥3 with the Glidescope AVL. There were no complications from awake flexible bronchoscopic intubation or video laryngoscopy. Conclusions: There is a high incidence of inability to obtain a view of the glottis with video laryngoscopy in patients with head and neck pathology, particularly airway masses. Level of Evidence: 3 Laryngoscope, 131:82–86, 2021